PERSEPSI MASYARAKAT DALAM KONTEKS SOSIAL EKONOMI TERHADAP PENDIDIKAN KETERAMPILAN INDUSTRI KREATIF KERAJINAN BAMBU DI KABUPATEN SIGI - Muchlis, Muchlis (Katalogis, 2017)
This study aims to determine the public perception of education skills of bamboo creative handycraft industry in improving the socio-economic life for the people in this district. This study is categorised as descriptive. This study aims to obtain a description and picture of the relationship between education skills and the creative industries bamboo craft skills with improved social life ekonomi. The data are collected by: observation, interviews, literature and documentation. Then, the data are analyzed by Chi-Square method. The results of this study concluded that: 1) The results show respondents who provide feedback and assessment of the implementation of the education skills of bamboo creative industriesin Sigi District are 11 respondents. There were 27.5% answered strongly agreed, 39 respondents or 97.0% answered agree, no one respondents answered disagree and no one respondents answered strongly disagree. It shows that the program implementation is supported and required because the publicunderstand that the program aims to progress rural welfare, 2) Educational skills programs of bamboo creative handicraft industry have significant impact for rural communities in Sigi District, as evidenced by analytical testing Chi-Square, where the result is: for social impacts scored 0.33, which proves that the level of relation between the social impact and education skills of the bamboo creative handicraft industry skills in Sigi District is only 33%. Mean while, the economic impact values obtained contingency coefficient is 0.28 which proves that the level of relation between the economic impact and the implementation of education skills of bamboo creative handicraft industryin Sigi District is only 28%.